A lightweight, high-performance composite foam insulation core material, preparation process and application thereof

By preparing lightweight and high-performance composite foam insulating core materials, the core burning and cracking problems existing in the curing process of existing composite cross-bar insulating core materials are solved, and the high insulation performance and lightweight characteristics of the material are achieved. It is suitable for High voltage composite cross-loading and other fields.

CN119008145BActive Publication Date: 2025-02-07NORTH CHINA ELECTRIC POWER UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411472110.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-07
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing composite cross-bond insulating core material is large in size, and there is a thermal concentration effect during the curing process, resulting in problems such as core burning and cracking inside the material, affecting its large-scale promotion and application in power lines.

Method used

The preparation process of lightweight and high-performance composite foam insulating core material includes mixing bisphenol A diglycidyl ether with methylnadic anhydride, and adding polymethacrylic methyl ester hollow microspheres and curing accelerator, through vacuum Immersion and segmented curing treatment, combined with the surface treatment of glass fiber cloth, produce materials with high insulation properties and lightweight properties.

Benefits of technology

It solves problems such as core burning and cracking inside the material, improves the comprehensive performance and production efficiency of the material, and is suitable for high-voltage composite cross-bursts and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119008145B_ABST
    Figure CN119008145B_ABST
Patent Text Reader

Abstract

The present invention discloses a lightweight, high-performance composite foam insulation core material, a preparation process and its application, and belongs to the technical field of electrical insulation materials. The present invention mixes MNA into the filling resin, and MNA can slow down the curing speed of lightweight composite materials and reduce the heat release to solve the problems of internal core burning, interface cracking and the like that may occur during the curing process. At the same time, MNA can also effectively fill the tiny defects in the resin, reduce the movement path of free charges, and reduce the current leakage caused by excessive local electric fields; the glass fiber cloth is further surface treated to obtain a lightweight, high-performance composite foam insulation core material with each part tightly combined, ensuring that it can be used in high-voltage environments and occasions with high insulation requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrical insulation materials, and in particular relates to a lightweight and high-performance composite foam insulation core material, a preparation process and an application thereof. Background Art

[0002] With the increasing requirements for low-carbon transformation of power grids, composite insulated crossarms are rapidly being widely used in power lines because they can save line corridor area and reduce the amount of steel used in line construction. However, due to the large volume of the existing composite crossarm insulation core and the heat concentration effect during the curing process, there are problems such as core burning and cracking inside the material, which is not conducive to the large-scale promotion and application of composite insulated crossarms. In addition, as a key component in the power system, the post composite insulator also faces the challenge of maintaining high insulation performance and structural integrity in extreme environments. Traditional post composite insulators usually use heavier materials, which not only increases construction and maintenance costs, but is also easily affected by external environmental factors in actual applications, resulting in performance degradation. Therefore, it is urgent to develop a composite core material with lightweight and high insulation performance, and improve its preparation process to improve the comprehensive performance and production efficiency of the material to meet the needs of composite insulation crossarms and post composite insulators. Summary of the invention

[0003] The purpose of the present invention is to provide a lightweight, high-performance composite foam insulation core material, a preparation process and its application, so as to solve the problems of internal core burning and cracking of the material existing in the prior art, thereby improving the comprehensive performance of the material, simplifying the manufacturing steps, and improving production efficiency, so that it can be widely used in the fields of high-voltage composite crossarms and the like.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] One of the technical solutions of the present invention is to provide a preparation process of a lightweight and high-performance composite foam insulation core material, comprising the following steps:

[0006] Preparation of high insulation material: bisphenol A diglycidyl ether and methyl nadic anhydride are mixed in a mass ratio of 100: (18-30), and then 3.5-4.5% of the total mass of bisphenol A diglycidyl ether and methyl nadic anhydride polymethyl methacrylate hollow microspheres are added, stirred evenly to obtain a mixture, and a curing accelerator is continuously added to obtain a high insulation material after curing;

[0007] Surface treatment of glass fiber cloth: immerse the glass fiber cloth in an isopropyl alcohol solution containing 2.5-3.5wt.% isopropyl triisostearyl titanate, take it out and perform heat treatment to complete the surface treatment of the glass fiber cloth;

[0008] Preparation of lightweight, high-performance composite foam insulation core material: The high-insulation material is wound with surface-treated glass fiber cloth, and the high-insulation material wound with the glass fiber cloth is impregnated with epoxy resin mixed with hexahydrophthalic anhydride, and the lightweight, high-performance composite foam insulation core material is obtained after curing.

[0009] The present invention uses a coupling agent triisostearyloxytitanate isopropyl ester (TTS) to perform surface treatment on the glass fiber cloth, aiming at enhancing the bonding performance between the glass fiber cloth and the epoxy resin matrix.

[0010] Preferably, the curing accelerator is 2,4,6-tris(N,N-dimethylaminomethyl)phenol.

[0011] Preferably, the added amount of the 2,4,6-tris(N,N-dimethylaminomethyl)phenol is 1% by mass of the mixture.

[0012] Preferably, in the preparation step of the high-insulation material, the specific steps of curing are: first treating at 50-60° C. for 2-3 hours, and then treating at 100-120° C. for 4-5 hours.

[0013] Preferably, the heat treatment is carried out at a temperature of 80-100° C. and for a time of 1.5-2.5 h.

[0014] Preferably, the impregnation is vacuum impregnation, and the specific steps of the vacuum impregnation include: placing the high-insulation material wrapped with glass fiber cloth into a vacuum bag coated with a release agent, and evacuating the bag to 10 -3 ~10 -1 Torr, introduce epoxy resin, keep impregnating for 1~2h, and complete vacuum impregnation.

[0015] More preferably, the release agent is US CRC 03301 high temperature resin release agent.

[0016] Preferably, the amount of hexahydrophthalic anhydride added to the epoxy resin mixed with hexahydrophthalic anhydride is 8-15% of the mass of the epoxy resin.

[0017] Preferably, the curing treatment after infiltration includes: pre-treatment at 80-100° C. for 10-12 hours, and then treatment at 120-160° C. for 4-5 hours to complete the curing.

[0018] The curing of the present invention adopts segmented processing, the purpose of which is to avoid cracking and deformation of the material during the curing process and reduce the generation of bubbles.

[0019] The second technical solution of the present invention is to provide a lightweight and high-performance composite foam insulation core material prepared according to the above-mentioned lightweight and high-performance composite foam insulation core material preparation process.

[0020] The third technical solution of the present invention is to provide an application of the above-mentioned lightweight and high-performance composite foam insulation core material in the preparation of composite insulation crossarms or pillar composite insulators.

[0021] The beneficial technical effects of the present invention are as follows:

[0022] The core material of the lightweight, high-performance composite foam insulation core material prepared by the present invention is epoxy resin filled with fully cured polymethyl methacrylate hollow microspheres. The material has a dense structure, a complete molecular chain, a high degree of cross-linking, and good electrical insulation performance, ensuring that it is suitable for high voltage environments and occasions with high insulation requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of the vacuum impregnation used in step 3 and step 4 in Example 1 of the present invention.

[0024] Figure 2 This is a graph showing the leakage current test results of the lightweight, high-performance composite foam insulation core material prepared in Examples 1-3 and Comparative Examples 1-2 of the present invention.

[0025] Figure 3 Graph showing leakage current test results of lightweight, high-performance composite foam insulation core materials prepared in Example 1 and Comparative Examples 3-6 of the present invention.

[0026] Figure 4 Comparative Example 6: The surface of the composite material prepared by the autoclave process.

[0027] Figure 5 Example 1: Surface of a composite material prepared by vacuum impregnation process. DETAILED DESCRIPTION

[0028] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0029] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0030] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0032] Some of the raw materials in the examples and comparative examples of the present invention are as follows:

[0033] Glass fiber cloth: specification is 9600 tex, the manufacturer is Zhejiang Jiaxing Jushi Co., Ltd.;

[0034] Bisphenol A diglycidyl ether (DGEBA): molecular weight 340.413, purity 98%, manufacturer is Baling Petrochemical Co., Ltd.;

[0035] Methylnadic anhydride (MNA): manufacturer is Zhongsheng Industrial Co., Ltd.;

[0036] 2,4,6-Tris(N,N-dimethylaminomethyl)phenol (DMP-30): purity 95%, manufacturer is Shanghai McLean Co., Ltd.;

[0037] Polymethyl methacrylate (PMMA) hollow microspheres: the manufacturer is Akzo Nobel;

[0038] Isopropyl triisostearyl titanate (TTS): The manufacturer is Nanjing Quanxi Chemical Co., Ltd.

[0039] Release agent: American CRC 03301 high temperature resin release agent.

[0040] Example 1

[0041] Step 1: Prepare high insulation material

[0042] 1. Premixing: Premix bisphenol A diglycidyl ether (DGEBA) and methyl nadic anhydride (MNA) at a mass ratio of 100:18.

[0043] 2. Add microspheres: Add 4% of the total mass of the pre-mixed product polymethyl methacrylate (PMMA) organic hollow microspheres and planetary stir to obtain a mixture. Then add 1% of the mass of the mixture 2,4,6-tris (N, N-dimethylaminomethyl) phenol (DMP-30) as a curing accelerator.

[0044] 3. Stirring to promote mixing: Place the mixed materials in a vacuum environment and perform planetary stirring again to ensure that all components are evenly distributed and remove bubbles.

[0045] 4. Staged curing: Place the material in an oven for pre-curing, set the temperature to 60°C for 2 hours. After completion, gradually increase the temperature to 120°C and maintain for 4 hours to complete the curing.

[0046] 5. After curing, let it stand and cool to obtain a high insulation material.

[0047] Note: The stirring process uses the MT-300 vacuum planetary stirrer of Melissi Company, the speed is designed to be 1200r / min, and the vacuum degree of the vacuum environment is set to 96kpa.

[0048] Step 2: Surface treatment of fiberglass cloth

[0049] 1. Select isopropyl alcohol as the solvent and prepare a 3wt.% concentration of triisostearyl titanate isopropyl (TTS) isopropyl alcohol solution, ensuring uniform mixing as the coupling agent solution.

[0050] 2. Soak the fiberglass cloth completely in the TTS isopropyl alcohol solution for 1 hour.

[0051] 3. Then take out the treated glass fiber cloth and heat treat it at 80°C for 2 hours to enhance the bonding strength between the coupling agent and the glass fiber. After treatment, cool it at room temperature.

[0052] Step 3: Pretreatment of vacuum bags and vacuum equipment

[0053] 1. Apply a layer of release agent evenly inside the vacuum bag to ensure that the final product can be demoulded smoothly.

[0054] 2. Overlap and tightly wrap the treated glass fiber cloth on the completely cooled high insulation material made in step 1, and place it neatly into the vacuum bag, ensuring that there are no wrinkles and bubbles, and that the fiber cloth is evenly distributed in the vacuum bag.

[0055] 3. Start the vacuum pump and gradually reduce the pressure in the vacuum container to 10 -3 Torr, for 30 minutes, exhausting as much air as possible.

[0056] Step 4: Introduce material and back pressure penetration

[0057] 1. While maintaining the vacuum state, the epoxy resin (DGEBA) mixed with hexahydrophthalic anhydride is introduced into the vacuum bag through the control valve, wherein the amount of hexahydrophthalic anhydride added is 10% of the mass of the epoxy resin.

[0058] 2. Due to the existence of the vacuum environment, the resin can quickly enter the pores of the glass fiber cloth. To ensure sufficient impregnation, this state is maintained for 2 hours to ensure that the epoxy resin is evenly distributed and fully penetrated into the glass fiber cloth.

[0059] Note: The schematic diagram of vacuum impregnation used in steps 3 and 4 is shown in Figure 1 .

[0060] Step 5: Solidification of the impregnation product

[0061] 1. Place the resin-infiltrated product together with the vacuum bag in an oven for a two-stage curing process.

[0062] 2. First, perform preliminary curing at 80°C for 12 hours so that the resin begins to gradually cure but does not completely harden, thereby maintaining the shape and structure of the material.

[0063] 3. Subsequently, the initially cured material is transferred to a high temperature environment of 120°C for final curing. This process lasts for 4 hours. Higher temperature and longer time can ensure that the resin is fully cured, achieving the best physical and chemical properties, and finally forming a strong composite material structure.

[0064] Step 6: Material demoulding and cooling and finishing

[0065] After curing is completed, the vacuum bag is removed from the high temperature environment and slowly cooled to room temperature to avoid the generation of internal stress caused by rapid cooling. After it is cooled to room temperature, demolding tools are used to assist in demolding, and trimming and cutting are performed as required to ensure that the length of each part reaches the required 1400mm to obtain a lightweight, high-performance composite foam insulation core material.

[0066] Example 2

[0067] Compared with Example 1, the only difference is that in step (1), DGEBA and MNA are mixed in a mass ratio of 100:24.

[0068] Example 3

[0069] Compared with Example 1, the only difference is that in step (1), DGEBA and MNA are mixed in a mass ratio of 100:30.

[0070] Comparative Example 1

[0071] Compared with Example 1, the only difference is that in step (1), DGEBA and MNA are mixed in a mass ratio of 100:6.

[0072] Comparative Example 2

[0073] Compared with Example 1, the only difference is that MNA is not added in step (1).

[0074] Comparative Example 3

[0075] Compared with Example 1, the only difference is that the MNA in step (1) is replaced by diethylenetriamine (DETA, from Tosoh Corporation of Japan, with a molecular formula of C4H13N3 and a molecular weight of 103.17. The mass ratio of the raw materials is DGEBA:DETA=100:12.

[0076] Comparative Example 4

[0077] Compared with Comparative Example 3, the only difference is the raw material ratio, DGEBA:DETA=100:18.

[0078] Comparative Example 5

[0079] Compared with Comparative Example 3, the only difference is the raw material ratio, DGEBA:DETA=100:24.

[0080] Comparative Example 6

[0081] Step 1: Prepare high insulation materials

[0082] 1. Premixing: Premix bisphenol A diglycidyl ether (DGEBA) and methyl nadic anhydride (MNA) at a mass ratio of 100:18.

[0083] 2. Add microspheres: Add 4% of the total mass of the pre-mixed product polymethyl methacrylate (PMMA) organic hollow microspheres and planetary stir to obtain a mixture. Then add 1% of the mass of the mixture 2,4,6-tris (N, N-dimethylaminomethyl) phenol (DMP-30) as a curing accelerator.

[0084] 3. Stirring to promote mixing: Place the mixed materials in a vacuum environment and perform planetary stirring again to ensure that all components are evenly distributed and remove bubbles.

[0085] 4. Staged curing: Place the material in an oven for pre-curing, set the temperature to 60°C for 2 hours. After completion, gradually increase the temperature to 120°C and maintain for 4 hours to complete the curing.

[0086] 5. After curing, let it stand and cool to obtain a high insulation material.

[0087] Note: The stirring process uses the MT-300 vacuum planetary stirrer of Melissi Company, the speed is designed to be 1200r / min, and the vacuum degree of the vacuum environment is set to 96kpa.

[0088] Step 2: Surface treatment of fiberglass cloth

[0089] 1. Select isopropyl alcohol as the solvent and prepare a 3wt.% concentration of triisostearyl titanate isopropyl (TTS) isopropyl alcohol solution, ensuring uniform mixing as the coupling agent solution.

[0090] 2. Soak the fiberglass cloth completely in the TTS isopropyl alcohol solution for 1 hour.

[0091] 3. Then take out the treated glass fiber cloth and heat treat it at 80°C for 2 hours to enhance the bonding strength between the coupling agent and the glass fiber. After treatment, cool it at room temperature.

[0092] Step 3: Vacuum bag-autoclave curing process

[0093] The treated glass fiber cloth is laminated with the mixed epoxy resin. Each layer is brushed to ensure that the resin can penetrate every corner of the glass fiber cloth and form a good bond. Repeat this step to ensure that the thickness reaches 1.3 times the required thickness. Then slowly and tightly wrap the laminated composite material around the insulating material in step 1, place it in a high temperature resistant vacuum bag, seal the vacuum bag, and perform vacuum extraction.

[0094] After vacuum extraction is completed, the vacuum bag is placed in an autoclave for curing. (The temperature is set to 150°C, the pressure is 1.5MPa, and it lasts for 3 hours.) Pay special attention to monitoring the temperature and pressure changes in the autoclave during the curing process to ensure the stability of the curing process.

[0095] Step 4: Material demoulding and cooling and finishing

[0096] After curing is completed, it is slowly cooled to room temperature to avoid the generation of internal stress caused by rapid cooling. After it is cooled to room temperature, demolding tools are used to assist in demolding, and trimming and cutting are performed according to requirements to ensure that the length of each part reaches the required 1400mm to obtain a lightweight, high-performance composite foam insulation core material.

[0097] Performance Test:

[0098] Test 1: Electrical performance test (based on DL / T 1580-2016 Technical Specifications for Core Rods for AC and DC Rod-Shaped Composite Insulators)

[0099] 1. Experimental materials and equipment:

[0100] The products of Examples 1-3 and Comparative Examples 1-6 (all with a length of 1400 mm); Rigio-DM3068 current sensor from Precision Electronics Corporation; electrode fixture, thermometer or temperature controller, surface treatment tools (such as cleaning cloth and ethanol).

[0101] 2. Experimental steps:

[0102] Cutting: Cut the product into specimens with a thickness of 30mm±0.5mm and a length and width suitable for testing. 4 specimens for each product, a total of 36 specimens.

[0103] Preliminary inspection: Check if there are any obvious defects or contamination on the surface of the product. If there are any, record them and prepare for surface treatment. (Clean the surface of the product with ethanol and a clean cloth to ensure that there is no grease, dust or other impurities. The cleaned product should be dried naturally or wiped dry with a clean cloth)

[0104] Boiling treatment: Prepare a deionized water solution containing 0.1% NaCl and heat it. Under boiling conditions, completely immerse the cleaned samples in deionized water containing 0.1% NaCl at the same time and keep it in boiling conditions for 100 hours. This process simulates the effect of high temperature and high humidity environment on the electrical properties of the product (the product will not float or touch the wall during the water bath to ensure uniform heating). After the boiling time is over, carefully remove the sample from the glass container.

[0105] Sample cooling and drying: After the water bath treatment is completed, carefully take out the product and place it in another glass container filled with 25°C deionized water for at least 15 minutes to allow it to gradually cool. After cooling, take out the sample and clean the surface again. Use a clean cloth to gently wipe the moisture on the surface of the sample to ensure that there is no residual moisture or impurities. Then use clean compressed air to blow away the residual moisture on the surface of the sample, paying special attention to the details and pores of the sample to ensure complete drying.

[0106] Leakage current test: Place the product on the current tester platform. Connect the flat electrode fixture to ensure that the electrode is in close contact with the product surface. Then apply 12kV voltage to the sample and measure the leakage current. Take the average value of the same product to ensure the minimum error.

[0107] The test results of Examples 1-3 and Comparative Examples 1-2 are shown in Figure 2 ,Depend on Figure 2It can be seen that under different ratios (DGEBA:MNA), the leakage current decreases with the increase of the MNA ratio. When the MNA ratio increases from 6 to 18, the leakage current decreases significantly (from 40.78 µA to 27.1 µA). After reaching the ratio of DGEBA:MNA=100:18, the leakage current still decreases but the amplitude is small when the MNA ratio is increased to 24 and 30. Finally, the leakage current is 25.78 µA at 100:30. In general, the addition of MNA can significantly reduce the leakage current in the DGEBA system, especially when the DGEBA:MNA ratio is 100:18. Although increasing the MNA ratio to 24 and 30 continues to reduce the leakage current, the reduction amplitude tends to be gentle, indicating that the moderate addition of MNA has a significant effect on improving electrical properties. In the optimal ratio of 100:18, the insulating effect of MNA is fully reflected, which may be related to its chemical structure and physical properties. MNA can increase the cross-linking density of the resin, making the molecular chains more closely arranged, thereby improving the insulation capacity of the material. At the same time, MNA can also effectively fill the tiny defects in the resin, reduce the movement path of free charges, and reduce the current leakage caused by excessive local electric fields. However, as the MNA ratio further increases to 24 and 30, although the leakage current still decreases, the magnitude of the decrease gradually decreases. This shows that when the proportion of MNA reaches a certain level, the gain effect begins to weaken, and the improvement of the electrical properties of the material enters the saturation stage. This phenomenon may be related to the distribution and interaction of MNA in the resin. Excessive MNA may lead to relative physical looseness or agglomeration, and even have a negative impact on the insulation performance. In addition, MNA is relatively expensive, so the industry can give priority to a ratio of 100:18 to obtain better performance and cost-effectiveness.

[0108] The test results of Example 1 and Comparative Examples 3-6 are shown in Figure 3 . Figure 3 It shows that even if the same type of curing agent as MNA is used to replace the same amount, the electrical properties of the prepared composite material are still improved by adding MNA.

[0109] Test 2: Thermally induced tensile test (based on GB / T 1447-2005 "Test methods for mechanical properties of fiber reinforced plastics")

[0110] Experimental materials and equipment: The test samples are the same as those in test 1, 4 samples for each product, a total of 36 samples. The CMT6104 electronic universal testing machine from Shenzhen Sansi Zongheng Technology Co., Ltd. is used.

[0111] Preliminary inspection: Check the product surface for obvious defects or contamination. If so, record and prepare for surface treatment. Clean the product surface with ethanol and a clean cloth to ensure there is no grease, dust or other impurities. The cleaned product should be dried naturally or wiped dry with a clean cloth.

[0112] Mechanical calibration: Check whether all parts of the electronic universal testing machine are normal and ensure that the equipment is in good working condition. Perform mechanical calibration on the CMT6104 electronic universal testing machine according to the calibration process in the equipment manual to ensure that the accuracy of the loading device and sensor is within the allowable range.

[0113] Test preparation: According to the tensile test standard (GB / T 1447-2005), set the tensile rate to 2mm / min. Carefully install the specimen into the center of the clamp of the electronic universal testing machine, ensuring that the specimen is vertical and firmly fastened in the clamp. Ensure that the center of the specimen is aligned with the axis of the force sensor to avoid test errors caused by eccentric loading.

[0114] Tensile test: Start the electronic universal testing machine. The equipment will apply tension to the sample at a preset tensile rate (2 mm / min). Collect the tensile stress-strain data of the sample in real time, and pay attention to the deformation and stress of the sample until the sample breaks. Record the maximum tensile strength when the sample breaks and calculate the average value.

[0115] Thermal induction treatment: 36 samples of the same type (four samples of each type) were selected and, after preliminary inspection, were placed evenly and neatly in a high-temperature oven (without contact and evenly heated), and set to 150°C. The temperature change was monitored to ensure that the temperature rose evenly. After 150°C, it was maintained for 48 hours. The oven was then closed and the samples were allowed to cool slowly to room temperature.

[0116] Thereafter, the treatment of two pairs of heat-induced samples was tested repeatedly, and the maximum tensile strength of the samples after heat induction when they broke was recorded, and the recorded data were averaged.

[0117] Compare the data before and after, and calculate the decrease in tensile strength after heat treatment.

[0118] The test results are shown in Table 1.

[0119] Table 1

[0120]

[0121] Table 1 shows that the initial tensile strength of Example 1 is 612 MPa, which is slightly lower than that of Examples 2 and 3, but it still remains at 598 MPa after heat treatment, indicating that this ratio has good comprehensive performance in practical applications. The strength decrease of Example 1 (DGEBA:MNA=100:18) is only 2.34%, which is close to the comparative example (2.29% and 2.27%), indicating that this ratio can still maintain a high mechanical property stability after high-temperature heat treatment.

[0122] At the ratio of DGEBA:MNA=100:18, the MNA content is moderate, which can promote the cross-linking reaction of DGEBA, improve the mechanical properties and thermal stability of the material, and avoid the problem of increased brittleness and decreased mechanical properties caused by excessive MNA content. Although the high MNA content of 100:24 and 100:30 has a high initial tensile strength, the strength decreases significantly after high-temperature heat treatment, indicating that in the case of excessive MNA, the cross-linking density of the material is too high, resulting in a decrease in mechanical properties after heat treatment.

[0123] Test 3: Power frequency breakdown test

[0124] Experimental materials and equipment: The test samples are the same as those in test 1, 4 samples for each product. The instrument used is a 50KV voltage breakdown tester from Beijing AVIC Times Instrument Equipment Co., Ltd.

[0125] Preliminary inspection: Check the product surface for obvious defects or contamination. If so, record and prepare for surface treatment. Clean the product surface with ethanol and a clean cloth to ensure there is no grease, dust or other impurities. The cleaned product should be dried naturally or wiped dry with a clean cloth.

[0126] Test preparation: Ensure that all parts of the voltage breakdown tester are functioning properly. Set the voltage ramp rate to 1kV / s according to the IEC 60243-1-2013 test standard. Carefully place the sample between the electrodes of the tester, ensuring that the sample is in good contact with the electrodes and is fully immersed in the oil tank. Ensure that the center of the sample is aligned with the center of the electrode to avoid test errors.

[0127] Breakdown test: Observe the voltage applied to the sample in real time until the sample breaks down, and record the breakdown voltage of each sample. The test results are shown in Table 2 (unit: kV / mm).

[0128] Table 2

[0129]

[0130] Table 2 shows that the breakdown voltage of the sample in Example 1 is 22.54, which is much higher than that of Comparative Examples 1-6. This shows that this ratio has good comprehensive performance in practical applications. The reason why Example 1 (DGEBA:MNA=100:18) stands out among different ratios and becomes the best choice is mainly because it has achieved an ideal balance between chemical crosslinking density, microstructure optimization, thermal stability and cost-effectiveness. MNA, as an anhydride curing agent, has a low heat release in the curing reaction with DGEBA, so it can reduce the heat release by slowing down the curing speed of lightweight composite materials to overcome problems such as internal core burning and interface cracking that may occur during the curing process. As the amount of MNA added increases, the breakdown voltage is further improved, but in Examples 2 and 3 after Example 1, it can be found that when MNA continues to be added, the rising trend of the breakdown strength of the material slows down, both between 22-23kV / mm.

[0131] In summary: Example 1 (DGEBA:MNA=100:18) performs best in terms of electrical and mechanical properties. In the electrical performance test, its leakage current was significantly reduced to 27.1 µA, and in the thermally induced tensile test, the initial tensile strength was 612 MPa, and the tensile strength after heat treatment only decreased by 2.34%. Compared with other ratios, although increasing the MNA ratio (such as 100:24 and 100:30) can further reduce the leakage current, the decrease in tensile strength after heat treatment is significantly larger, 5.25% and 8.05%, respectively, resulting in increased material brittleness. At the same time, MNA is expensive, and excessive use will lead to an increase in overall costs. Therefore, the DGEBA:MNA=100:18 ratio achieves the best balance in electrical properties, mechanical properties and thermal stability, and also has advantages in cost-effectiveness, making it the most ideal choice.

[0132] In addition, the surface of the composite material prepared by the autoclave process in Comparative Example 6 is Figure 4 , Example 1 Surface part of the composite material prepared by vacuum impregnation process Figure 5 Compared with the vacuum impregnation method of Example 1, the composite material interface produced by the method described in Comparative Example 6 has some cracks, and the glass fiber and the internal insulating material are not tightly combined. The effect is quite different from the vacuum impregnation method, which is consistent with the test results of the leakage current. When the voltage is applied, the current will flow through these defective areas, resulting in an increase in the leakage current. At the same time, the uneven interface distribution will also lead to stress concentration, which greatly reduces the final tensile strength, and the fracture mode of the tensile specimen may be more fragile, showing brittle fracture rather than ductile fracture.

[0133] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A process for preparing a lightweight, high-performance composite foam insulation core material, characterized in that: The following steps are involved: Preparation of high insulation material: bisphenol A diglycidyl ether and methyl nadic anhydride are mixed in a mass ratio of 100: (18-30), and then 3.5-4.5% of the total mass of bisphenol A diglycidyl ether and methyl nadic anhydride polymethyl methacrylate hollow microspheres are added, stirred evenly to obtain a mixture, and a curing accelerator is continuously added to obtain a high insulation material after curing; Surface treatment of glass fiber cloth: immerse the glass fiber cloth in an isopropyl alcohol solution containing 2.5-3.5wt.% isopropyl triisostearyl titanate, take it out and perform heat treatment to complete the surface treatment of the glass fiber cloth; Preparation of lightweight, high-performance composite foam insulation core material: The high-insulation material is wound with surface-treated glass fiber cloth, and the high-insulation material wound with the glass fiber cloth is impregnated with epoxy resin mixed with hexahydrophthalic anhydride, and the lightweight, high-performance composite foam insulation core material is obtained after curing.

2. The process for preparing the lightweight and high-performance composite foam insulation core material according to claim 1, characterized in that: The curing accelerator is 2,4,6-tris(N,N-dimethylaminomethyl)phenol.

3. The process for preparing the lightweight and high-performance composite foam insulation core material according to claim 2, characterized in that: The added amount of the 2,4,6-tris(N,N-dimethylaminomethyl)phenol is 1% of the mass of the mixture.

4. The process for preparing the lightweight and high-performance composite foam insulation core material according to claim 1, characterized in that: In the preparation steps of the high insulation material, the specific steps of curing are: first treating at 50-60° C. for 2-3 hours, and then treating at 100-120° C. for 4-5 hours.

5. The process for preparing the lightweight and high-performance composite foam insulation core material according to claim 1, characterized in that: The heat treatment temperature is 80-100° C. and the time is 1.5-2.5 hours.

6. The process for preparing the lightweight and high-performance composite foam insulation core material according to claim 1, characterized in that: The impregnation is vacuum impregnation, and the specific steps of the vacuum impregnation include: placing the high insulation material wrapped with glass fiber cloth into a vacuum bag coated with a release agent, and evacuating the bag to 10 -3 ~10 -1 Torr, introduce epoxy resin, keep impregnating for 1~2h, and complete vacuum impregnation.

7. The process for preparing a lightweight, high-performance composite foam insulation core material according to claim 1, characterized in that: The amount of hexahydrophthalic anhydride added to the epoxy resin mixed with hexahydrophthalic anhydride is 8-15% of the mass of the epoxy resin.

8. The process for preparing a lightweight, high-performance composite foam insulation core material according to claim 1, characterized in that: The curing treatment after infiltration includes: pretreatment at 80~100℃ for 10~12h, and then treatment at 120~160℃ for 4~5h to complete the curing.

9. A lightweight and high-performance composite foam insulation core material obtained according to the preparation process of the lightweight and high-performance composite foam insulation core material according to any one of claims 1 to 8.

10. Use of the lightweight, high-performance composite foam insulation core material according to claim 9 in the preparation of composite insulating crossarms or post composite insulators.

Citation Information

Patent Citations

  • Light foam sandwich composite material insulating rod and preparation methods thereof

    CN102136325A

  • Low dielectric constant hollow carbon sphere / epoxy resin composite material and preparation method thereof

    CN103756253A